A systematic review of human papillomavirus vaccination among US adolescents. Issue 3 (16th April 2021) - Mansfield, Lisa N.; Vance, Ashlee; Nikpour, Jacqueline A.; Gonzalez‐Guarda, Rosa M.
Abstract: The human papillomavirus (HPV) causes many anogenital and oral cancers affecting young adults in the United States. Vaccination during adolescence can prevent HPV‐associated cancers, but vaccine uptake among adolescents is low and influenced by factors serving as barriers and facilitators to HPV vaccination. In this systematic review, we synthesized research using the socioecological framework model to examine individual‐level, relationship‐level, community‐level, and societal‐level factors that influence HPV vaccine initiation and completion among US adolescents. The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines were used to guide the methodology for this review. An electronic search was conducted in January 2020 using PubMed, Cumulative Index of Nursing and Allied Health Literature, ProQuest Central, Scopus, and American Psychological Association PsycInfo databases. The Joanna Briggs Institute tools were used to assess the quality for the 57 studies included in this review. The most consistent influences of HPV vaccination included age at vaccination, awareness, and knowledge about HPV vaccination, socioeconomic status, insurance status, race/ethnicity, and preventative care behaviors at the individual level. Provider recommendation, familial/peer support of vaccination, and parental health behaviors were influences at the relationship level. Although fewer findings elucidated community‐level and societal‐level influences, high‐poverty areas, high‐risk communities with large proportions of racial/ethnic minority groups, healthcare facilities servicing children, and combined health policies appear to serve as facilitators of HPV initiation and completion. Findings from this review can inform culturally relevant and age‐specific interventions and multi‐level policies aiming to improve HPV vaccination coverage in the United States.